PCA analysis of soil geochemical data and environmental assessment of the pre-mining Shuteen area, South Mongolia - Batkhishig, Bayaraa; Manzshir, Bayarbold; Munkhtsengel, Baatar; Noriyoshi, Tsuchiya (Mongolian Geoscientist, 2020)
There are widespread mineralized systems, occurrences, deposits that occurred in the South Gobi, Mongolia, where many of them already undergone mining activity. However, not all of them have a pre-mining environmental assessment. The Shuteen area is one of these highly prospective areas for mining; due to the porphyry copper system observed, prospecting and exploration projects have been carried out since 1980. Numerous prospecting and exploration works have been done during 1997–2007 and suspended last decade because of economic and political reasons. The area is located in a Gobi-desert environment and wind plays a main role in the transport and mobility of the elements. This research was conducted to assess the environmental condition of the area, based on soil, dry river sediment, and drinking water geochemistry. We are expecting the area has a naturally high concentration of some heavy metals in soil, concerning the geology and mineralization. The results show that the heavy metal content in the soil does not exceed the permissible limit of the Mongolian National standard on soil quality. Whereas, the water samples contain F- above the permissible limit guided in the Mongolian National Standard on drinking water quality. The unusual chemical composition of the water is related to the soil composition characteristic of the Gobi region. They are characterized by low alkali, high salinity and mineral/water ratios are high. Environmental assessment surveys determine the characterization of an areal geochemical base prior the development of later exploration or mining project, might have affect it and establish the initial environmental status.